John of God: the globalization of Brazilian faith healing - Rocha, Cristina (Oxford University Press, 2017)
This work investigates the growing number of Western followers of John of God, a faith healer who has drawn hundreds of thousands of people, including Oprah Winfrey, to his healing center in Brazil by purportedly performing miraculous surgeries on people with a kitchen knife and no anesthetics.